When proteomics meets structural biology. - Zhou, M; Robinson, C (2010)
Recent progress in proteomics has identified vast arrays of interacting proteins together with knowledge of their post-translational modifications. A key challenge is to integrate this information with homology modelling and structural biology to provide a topological or even an atomic context for these modifications. Mass spectrometry (MS) is ideally placed to bring together these largely independent disciplines, being already established in proteomics and rapidly emerging in structural biology. By using MS-based approaches to probe the subunit stoichiometry of intact complexes, interaction networks and subunit packing can be defined, leading ultimately to 3D models. In this review, we discuss how superimposing proteomics information onto both low-resolution 3D models and high-resolution atomic structures can reveal new insight into function.